Environmental Drivers of Habitat Use by Hawksbill Turtles (Eretmochelys imbricata) in the Arabian Gulf (Qatar) - Marshall, Christopher D.; Cullen, Joshua A.; Al-Ansi, Mehsin; Hamza, Shafeeq; Abdel-Moati, Mohamed A. R. (Frontiers in Marine Science, 2020)
Understanding the environmental drivers of movement patterns are critical to the protection, management and recovery of endangered species. The Arabian Gulf is considered to be the hottest marine system in the world and is known for its extreme environmental conditions that pose substantial physiological stress on marine organisms living there. Satellite tags were deployed on hawksbill turtles in the Arabian Gulf and quantitative ecological modeling (i.e., Bayesian state-space models and GAMMs) was used to provide new insights into the ecological basis of observed hawksbill movement and behavior. Hawksbills used a relatively large core area in the southeast Arabian Gulf when transit and area-restricted search behaviors were included. The numerous hotspots identified suggest that important habitat occurs along a large area of the Qatari eastern coastline and into Saudi Arabia. Offshore islands with fringing reef habitat and deep-water habitats near the 30–50 m isobaths were intensely used. Hawksbills made seasonal migrations to deep-water habitat during summer months, typically once SST reached ∼33°C and bottom temperature reached ∼32°C. These data provide valuable information to managers seeking to conserve hawksbills in the region. Our data also provide a context to understand the underlying physiological, energetic and behavioral drivers of hawksbill movement in the Arabian Gulf. Future studies should include the use of biologging devices, benthic surveys, and dietary biomarkers to better understand the seasonal migrations of Arabian Gulf hawksbills to this deep-water region.